On political activism in digital games - Cermak-Sassenrath, Daniel (MedieKultur: Journal of media and communication research, 2018)
This project investigates how players of digital games apply their own play with the intent to transmit political messages to other players. Acts of activism are collected from a sample of commercial multiplayer online games; three taxonomies are proposed of which one is used to present the findings, and popular patterns or structures of activism are identified. It is found that in-game activism often takes its cue from activism in everyday life, but that some original topics emerge, for example, the ownership of virtual worlds and practices of in-game political activism such as novel forms of rallies. Current political activism often appears to utilize generic and widely-shared game mechanics, rather than mechanics specific to individual games or genres. Games are therefore selected for their topics, availability, and costs, and popularity with the target audience